Assessing Employee’s Perception on Digitalization of Recruitment Function in the Elearning Industry - A.Sengupta, Dr.S.Lalwani, Dr. S.Goswami, Dr. A.Ghosh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Recruitment is a key functional area of the human resource management process. Streamlining the entire process and making it effective and efficient whilst selecting the most appropriate candidate(s) as future asset(s) of the organization is the core of the process. Digitalization has enabled employing the recruitment strategies in an effective manner. E-recruitment as it is known, enables every aspect of recruitment process to be technology enabled, enhancing the overall process, and also enables a prospective candidate to have and understand a broader view of the organization. It is important to gauge people’s perception towards the effectiveness of any technology driven change in an organization. The main purpose of the present work is to assess the employee’s perception on digitalization of recruitment functions in the e-learning industry. Online survey method was adopted for this study. A total of 107 sample respondents were selected from e-learning companies. 5-point Likert scale was developed on employee’s perception of digitalization of recruitment functions under various dimensions. Mean, ‘SD’ and one sample-t test has been utilized for data analysis. The study concluded that significant difference exists in the perception of employees towards digitalization of recruitment functions in the e-learning industry